Rapid Covalent Labeling of Membrane Proteins on Living Cells Using a Nanobody–Epitope Tag Pair - Cabalteja, Chino C.; Sachdev, Shivani; Cheloha, Ross W. (Bioconjugate chemistry, 2022)
Synthetic molecules that form a covalent bond upon binding to a targeted biomolecule (proximity-induced reactivity) are the subject of intense biomedical interest for the unique pharmacological properties imparted by irreversible binding. However, off-target covalent labeling and the lack of molecules with sufficient specificity limit more widespread applications. We describe the first example of a cross-linking platform that uses a synthetic peptide epitope and a single domain antibody (or nanobody) pair to form a covalent linkage rapidly and specifically. The rate of the cross-linking reaction between peptide and nanobody is faster than most other biocompatible cross-linking reactions, and it can be used to label live cells expressing receptor–nanobody fusions. The rapid kinetics of this system allowed us to probe the consequences on signaling for ligand cross-linking to the A2A-adenosine receptor. Our method may be generally useful to site-specifically link synthetic molecules to receptors on mammalian cell surfaces.